6x-13x-2=10x-24

Simple and best practice solution for 6x-13x-2=10x-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-13x-2=10x-24 equation:


Simplifying
6x + -13x + -2 = 10x + -24

Reorder the terms:
-2 + 6x + -13x = 10x + -24

Combine like terms: 6x + -13x = -7x
-2 + -7x = 10x + -24

Reorder the terms:
-2 + -7x = -24 + 10x

Solving
-2 + -7x = -24 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-2 + -7x + -10x = -24 + 10x + -10x

Combine like terms: -7x + -10x = -17x
-2 + -17x = -24 + 10x + -10x

Combine like terms: 10x + -10x = 0
-2 + -17x = -24 + 0
-2 + -17x = -24

Add '2' to each side of the equation.
-2 + 2 + -17x = -24 + 2

Combine like terms: -2 + 2 = 0
0 + -17x = -24 + 2
-17x = -24 + 2

Combine like terms: -24 + 2 = -22
-17x = -22

Divide each side by '-17'.
x = 1.294117647

Simplifying
x = 1.294117647

See similar equations:

| -13+6x=21+4x | | 4m+2=8m-3 | | 3e+1=5 | | 2.7+f=3*5 | | 4x^3+108=0 | | 8x+7=5x+34 | | 2(4+2k)+10=10 | | -6+8+3p=4p-7 | | 2x-11=25-4x | | 2+6e=19 | | 3x+26=11x-70 | | 4x-3=13-111 | | 4(2x+3)=4x-5-3 | | 2x+58=8x+10 | | 3x+1=x-2 | | 10x-1=4x-10+8 | | 5r^2= | | 5(3x-4)+3(x+2)= | | 400+50g+.06(400+50g)=742 | | 2x-5=-4x+11 | | -3k+2=6k-8-1 | | 6.18x-2000=0 | | 3x^4= | | 11x+6=83 | | -3m=33 | | .06(400+50g)=742 | | .06(s+50g)=742 | | 2a+3a=10 | | 4y-5=8 | | 4x+3x-13+20=23 | | 10K-3K=28 | | 3x+8=10x+3 |

Equations solver categories